Stduy Pollen grains of family dicot in University of Al- Qadisiyay - Ama'l Abd Al-Ridha O'bead (Al-Qadisiyah Journal of Pure Science, 2017)
The anatomical characterstic Pollen grains of family dicotyledonae in University of Al-Qadisiyay Punicaceae of Punica, Rosaceae of Rosa, Verbenaceae of Verbena, Scrophulariaceae of Antrrhinum , Apocynaceae of Nerium& Chatharanthus, Convolvulaceae of Convolvulus &Cuscuta , Myrtaceae of Eucalyptus& Callistemon, Malvaceae of Gossypium ,Hibiscus, Althaea& Malva .The study characters pollen grains of many different between of species,same characters importance species of the one family